Pengaruh Suhu dan Waktu Pengeringan Terhadap Sifat Kimia dan Sensori Teh Celup Herbal Daun Putri Malu (Mimosa pudica Linn.) - Christiani, Elia Agatha; Kencana Putra, I Nengah; Suparthana, I Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2021)
The objective of this study was to know the effect of time and drying temperature on the chemical and sensory properties of herbal tea bag made from Mimosa pudica Linn. leaves and to know the right time and drying temperature to get the best chemical and sensory properties of herbal tea bag of Mimosa pudica Linn. leaves. This research used a Completely Randomized Design with two factors i.e. drying temperature (40°C, 50°C, and 60°C) and drying time (110, 130, and 150 minutes). All of the treatments were repeated two times to obtain 18 units of experiments. The data obtained were analyzed by analysis of variance (ANOVA) and if the treatment had a significant effect, then it was followed by The Duncan Multiple Range Test (DMRT). The results showed that the interaction of time and drying temperature had a significant effect (P<0,05) on total flavonoids, but no significant effect (P>0,05) on the moisture and extract content, total phenolics, and IC50 valued. The drying temperature had a significant effect on the moisture content and IC50 valued, while the time and drying temperature had a significant effect on the extract content and taste (scoring test). The results showed that the drying temperature of 50°C for 110 minutes was the best treatment, where the herbal tea produced had a criteria: moisture content 6.50%; extract content 14.70%; total phenolics 25.19 mg GAE/g dry weight; total flavonoids 16.07 mg QE/g dry weight; IC50 valued 74.45 ppm; the color, flavor, and taste were slightly liked; an overall acceptance neutral; and the taste was slightly bitter.